Transferable Resistance to Highest Priority Critically Important Antibiotics for Human Health in Escherichia coli Strains Obtained From Livestock Feces in Uruguay - Coppola, Nadia; Freire, Bibiana; Umpiérrez, Ana; Cordeiro, Nicolás F.; Ávila, Pablo; Trenchi, Gustavo; Castro, Gustavo; Casaux, María Laura; Fraga, Martín; Zunino, Pablo; Bado, Inés; Vignoli, Rafael (Frontiers in Veterinary Science, 2020)
The aim of this work was to detect Escherichia coli isolates displaying resistance to oxyimino-cephalosporins, quinolones and colistin in feces from livestock in Uruguay. During 2016-2019, fecal samples from 132 broiler and layer chicken flocks, 100 calves, and 50 pigs, were studied in Uruguay. Samples were cultured on MacConkey Agar plates supplemented with ciprofloxacin, ceftriaxone, or colistin. E. coli isolates were identified by mass spectrometry and antibiotic susceptibility testing was performed by disk diffusion agar method and colistin agar test. Antibiotic resistance genes were detected by polymerase chain reaction and sequencing. The most frequently detected resistance gene was qnrB19, recovered from 87 animals. Regarding plasmid-mediated quinolone resistance genes, qnrS1 was the second in prevalence, (23 animals) followed by qnrE1, found in 6 chickens and two calves. Regarding resistance to oxyimino-cephalosporins, 8 different 𝛃-lactamase genes were detected: blaCTX-M-8 and blaCMY-2 were found in 23 and 19 animals, respectively; next, blaCTX-M-2 and blaSHV-12 in 7 animals each, followed by blaCTX-M-14 in 5, blaCTX-M-15 and blaSHV2a in 2, and blaCTX-M-55 in a single animal. Finally, the mcr-1 gene was detected only in 8 pigs from a single farm, and in a chicken. Isolates carrying blaCMY-2 and blaSHV-12 were also found in these animals, including 3 isolates featuring the blaCMY-2 / mcr-1 genotype. To the best of our knowledge, this is the first work in which the search for transferable resistance to highest priority critically important antibiotics for human health is carried out in chickens and pigs chains of production animals in Uruguay.